The Effect of Creative Problem Solving Model Assisted by Picture Series Media on Creative Thinking Ability - Muh. Agus; Tarman A Arif; Muhammad Akhir (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to describe the effect of creative problem solving models assisted by serial images on creative thinking skills. The type of research used in this study is a quasi experimental design type nonequivalent control group design. The population in this study were all students of Cluster I, Somba Opu sub-district, Gowa district, totaling 329 students with a total sample of 60 using cluster random sampling technique. The data collection technique used is a test technique to determine the ability to think creatively by giving essay questions. The results of the study based on hypothesis testing about the effect of the Creative Problem Solving model assisted by serial picture media on students' creative thinking skills in the control and experimental class posttest using the independent sample t test, obtained a significant value of 0.00 less than 0.05 so it can be stated that creative problem solving model assisted by serial picture media has an effect on students' creative thinking skills.